Design And Development Of A Web-Based Disaster Incident Reporting Information System For BPBD Binjai - Aminmahrup, Ridwan Setiawan; Simatupang, Andri Josua Ruhut; Nasution, Muhammad Fariyandi; Kurniawan, Fahmi (Universitas Dehasen Bengkulu, 2025)
This study aims to design and develop a web-based information system for recording disaster incident reports at BPBD Binjai. The system is developed to assist officers in managing disaster report data more efficiently. Currently, the data collection process is still conducted manually, such as writing on paper or using basic applications like Microsoft Excel. This condition results in difficulties when retrieving old data, a high risk of data loss, and slower data entry processes. The system development follows the waterfall method, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. The final result of this study is expected to improve the efficiency of disaster incident report management, accelerate decision-making processes, and serve as a digital solution that supports the duties of BPBD Binjai in disaster response and management.